The investigation of co-combustion process for synergistic effects using thermogravimetric and kinetic analysis with combustion index - ÖZVEREN, UĞUR (ELSEVIER, 2021)
In an attempt to discover the synergistic mechanisms of co-combustion processes, a combination of thermogravimetric and kinetic analysis was conducted in this study to investigate the co-combustion characteristics of Imbat coal, almond shell, and their different blend ratios. The TGA experiments under atmospheric conditions (21% O2, 79% Ar) with 45 mL/min were carried out at a given temperature between 25 ?C and 1200 ?C by setting the heating rates at 10, 20 and 30 K/min. TGA curves showed the co-combustion process took place in two main stages: the volatile combustion zone and the fixed-carbon combustion zone. Furthermore, model fitting method based Coats-Redfern kinetic model was applied on TGA data of Imbat coal (IC), almond shell (AS), and their blends to calculate the kinetic parameters including reaction order, pre-exponential factor, and activation energy. Kinetic calculations were performed separately for both different combustion stages. The kinetic model were examined by coefficient of determination (R2) and results showed that R2 value changes between 0.8833 and 0.9982. The co-combustion characteristics of blends are synergistically influenced by the blend ratio between Imbat coal and almond shells such as combustion indexes, ignition temperature and peak temperatures. Combustion index values were increased from 2.95E-08 to 1.32E-07 for heating rate of 10 K/min, from 3.63E-08 to 3.25E-07 for heating rate of 20 K/min and from 3.63E to 08 to 6.1E-07 for 30 K/min. Results show that biomass can be burned with low-rank coals effectively, which means co-combustion technology provides more environmentally friendly way for energy generation.
Keywords: MICROALGAE COMBUSTION; THERMAL-DECOMPOSITION; BIOMASS COCOMBUSTION; SEWAGE-SLUDGE; CO2 CAPTURE; COAL; PYROLYSIS; AIR; TORREFACTION; BEHAVIOR